A constrained A* approach towards optimal path planning for an unmanned surface vehicle in a maritime environment containing dynamic obstacles and ocean currents. (1st December 2018) - Singh, Yogang; Sharma, Sanjay; Sutton, Robert; Hatton, Daniel; Khan, Asiya
Abstract: Efficient path planning is a critical issue for the navigation of modern unmanned surface vehicles (USVs) characterized by a complex operating environment having dynamic obstacles with a spatially variable ocean current. The current work explores an A* approach with an USV enclosed by a circular boundary as a safety distance constraint on generation of optimal waypoints to resolve the problem of motion planning for an USV moving in a maritime environment. Unlike existing work on USV navigation using graph based methods, this study extends the implementation of the proposed A* approach in an environment cluttered with static and moving obstacles and different current intensities. The study also examines the effect of headwind and tailwind currents moving in clockwise and anti clockwise direction respectively of different intensities on optimal waypoints in a partially dynamic environment. The performance of the proposed approach is verified in simulations for different environmental conditions. The effectiveness of the proposed approach is measured using two parameters, namely, path length and computational time as considered in other research works. The results show that the proposed approach is effective for global path planning of USVs. Highlights: The current study proposes a grid based path planning approach considering static and moving obstacles together with sea surface currents. The present study optimizes the path length by constraining USV with a fixed safety distance from the obstacle. The effect of headwind and tailwind surface ocean currents on path planning is analysed.